The role of traditional and modern financial performance metrics in predicting shareholders’ wealth - Alahakoon, A.M.U.M.P. (University of Jaffna, 2020)
Shareholders are considered as one of the major key players of an organization. Present arena, stakeholders of the organizations attempt to find a timely and reliable metric to predict shareholders’ wealth. The study aims to identify the relationship between traditional and modern financial metrics with shareholders’ wealth. ROA and ROE were considered traditional financial performance metrics, while EVA was considered modern. Data of 24 firms based on the highest market capitalization, over five years from 2013-2017, were extracted from their annual reports. Descriptive Statistics, correlation analysis, multicollinearity, and the pooled ordinary least square methods were used to analyze data. The correlation analysis results denoted a positive relationship between ROA, ROE, and EVA with MVA. Hypotheses were tested based on the pooled regression results. The findings of the study revealed that ROA and EVA have a significant positive relationship with MVA, while the EVA is making the highest relationship towards MVA. Thus, it is recommended that the financial managers focus more on EVA in predicting shareholders’ wealth.
Keywords: economic value added (EVA); return on assets (ROA); market value added (MVA); return on equity (ROE)